THE ROLE OF THE PRINCIPLE OF RELIGIOUS TOLERANCE IN ENSURING PEACE IN OUR COUNTRY - Kamilov Abdusalim Abdullayevich (Western European Studies, 2025)
This article examines the historical roots of religious tolerance and reflects on the reforms being implemented in the field of religious tolerance in Uzbekistan today
Keywords: Judaism; Christianity; Islam